Cost effectiveness of a protocol using palivizumab in preterm infants - Yolanda Hernández-Gago; Marina Lombardero-Pin; Casilda Ortega de la Cruz; Pablo A. Maciuniak; Alicia Díez del Pino (Elsevier, 2017)
Objective: The main objective was to evaluate the cost-effectiveness of protocol use of palivizumab in premature established by consensus in our Hospital comparing it based on the recommendations of various Scientific Societies. As a secondary objective risk factors and severity of hospitalized patients attending the established protocol in our Hospital were analyzed. Methods: The study period was 4 seasons with the expanded protocol (retrospective data) versus 2 with restricted or agreed protocol (prospective data). The perspective of the study was the Health System, including the costs of hospitalization and palivizumab our center. The calculation of the effectiveness was determined with the admission rate of premature patients stratified by weeks of gestational age <29, <32; and <35. For the analysis of risk factors and severity in patients admitted seasons with the new protocol are collected prospectively clinical data and environmental and social factors. Results: In the range of gestational age <29 years old and <32 greater effectiveness of the extended protocol was not demonstrated against the consensus. Only more effective for EG <35 in the accumulated data and comparing seasons 12/13 and 08/09 to 13/14 for individual data was observed. This range has an associated incremental cost effectiveness ratio of € 53 250,07 (range: € 14 793,39 to € 90 446,47 for singles data and € 50 525,53 (€ 28 688.22 to € 211 575,65) for accumulated. The establishment of this protocol in our center meant an average saving per season € 169 911,51. A cost- effectiveness of the extended protocol appropriate relationship is found if the cost of palivizumab per patient was less than € 1 206,67 (calculated for maximum use of the vial) and a higher rate of hospitalization of 9.21%. Children entering the season with the new protocol (season 12/13 and 13/14) are 63.4% in children under 3 months and 90% are term infants who do not belong to any population at risk, while many of them have associated risk factors you vary as have school-age siblings, rural residence, parental smoking, poor educational background of parents, lack of artificial feeding and family history of allergy. Conclusions: The consensus protocol has not been a significant increase in hospitalization rates in preterm infants <32 weeks gestational age patients. In those <35 has been observed a higher rate of hospitalization, with a very unfavorable cost-effectiveness for all clinical scenarios valued relationship.